2011
DOI: 10.1002/elps.201000625
|View full text |Cite
|
Sign up to set email alerts
|

Interdigitated comb‐like electrodes for continuous separation of malignant cells from blood using dielectrophoresis

Abstract: In this paper, a method for continuous flow separation of circulating malignant cells from blood in a microfluidic device using dielectrophoresis is discussed. Separation of MDA231 breast cancer cells after mixing with normal blood cells was achieved with a level of accuracy that enabled precise counting of the malignant cells, separation and eventually, sub-culturing. MDA231 cells were separated from the blood to a daughter channel using two pairs of interdigitated activated comb-like electrode structures. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
126
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(133 citation statements)
references
References 60 publications
1
126
0
Order By: Relevance
“…A majority of DEP cancer cell isolation techniques use model cancer cell lines spiked in buffer media or diluted blood; such techniques include DEP flowfield fractionation (DEP-FFF) [33][34][35][36], insulative and contactless DEP [37][38][39][40], and streamline separations using angled electrodes [41][42][43][44]. These studies separate cancer cells from other blood constituents based on their differences in DEP response in a specific applied frequency range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of DEP cancer cell isolation techniques use model cancer cell lines spiked in buffer media or diluted blood; such techniques include DEP flowfield fractionation (DEP-FFF) [33][34][35][36], insulative and contactless DEP [37][38][39][40], and streamline separations using angled electrodes [41][42][43][44]. These studies separate cancer cells from other blood constituents based on their differences in DEP response in a specific applied frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…This binary separation mechanism makes DEP an attractive tool for cell separation, as DEP requires no biochemical treatment or labeling to achieve high capture efficiency and purity. However, to date, studies using DEP methods for CTC capture have only reported high capture performance for model cancer cell lines spiked in preprocessed blood with concentrations ranging from one cancer cell per 10 4 -10 6 blood cells [33,34,36,39,40,42,44]. The commercially licensed ApoStream ™ (ApoCell) system, which uses DEP-FFF, has reported capture efficiencies in the range of 50-80% for ovarian and breast cancer cell lines spiked in peripheral blood mononuclear cells (PBMCs) with concentrations as low as one cancer cell per 10 6 blood cells, but noted that efficiency decreased after running samples through the system multiple times to increase capture purity [35].…”
Section: Introductionmentioning
confidence: 99%
“…Angled electrode structures have also been used as "funnels" to guide particle motion within a channel or as part of the function of a microsystem [55][56][57][58][59]. As DEP separators, angled electrode structures have been found favorable in their reliance on negative DEP for inducing forces of different strength on particles of different properties.…”
Section: Dielectrophoretic Separation Using Angled Electrodesmentioning
confidence: 99%
“…6,7 Blood cells can be separated by hydrodynamic [8][9][10][11][12][13][14][15][16][17][18] and electrokinetic forces. [19][20][21][22][23][24][25] Many disc-like microfluidic chips [26][27][28][29] have been integrated with compact disk (CD) readers that can a) Author to whom correspondence should be addressed. Electronic mail: hcchang@mail.ncku.edu.tw.…”
mentioning
confidence: 99%
“…One electrokinetic technology, DEP, has been widely used for manipulating, separating, 33,39 focusing, 40 and concentrating 41 cells/ bacteria/DNA in microfluidic channels. However, the most of DEP with blood application have been developed continuous flow separation of cancer cell 22,42 from dilute blood sample, few works with plasma separation 20 and blood cell separation. 23 In addition, Takashi's group 20 developed a chip to separate blood cells from a diluted whole blood sample using negative dielectrophoretic force.…”
mentioning
confidence: 99%